Gut Microbiota: An Integral Moderator in Health and Disease - Feng, Qingqing; Chen, Wei-Dong; Wang, Yan-Dong (Frontiers in Microbiology, 2018)
The gut microbiota, as the main member in gut microecology, is an essential mediator in health and disease. The gut microbiota interacts with various organs and systems in the body, including brain, lung, liver, bone, cardiovascular system and others. Microbiota-derived metabolites such as the short chain fatty acid (SCFA) butyrate are primary signals, which link the gut microbiota and physiology. Recently, the gut microbiota has been identified as the origin of a number of diseases by influencing the related cell signaling pathways such as WNT/beta-catenin pathway in colorectal cancer and T cell receptor signaling in the central nervous system. Moreover, several microRNAs participate in signaling networks through the intervention of the gut microbiota. The interaction between the gut microbiota and miRNAs plays a crucial role in vascular dysfunction and hepatocellular carcinoma (HCC). In this review, we will report and discuss recent findings about the crosstalk between the gut microbiota and physical organs and how the gut microbiota and miRNAs regulate each other while influencing the host via genes, proteins or metabolites.